Clinical outcomes of hepatitis C virus elimination using glecaprevir and pibrentasvir in hemodialysis patients: A multicenter study. Issue 5 (27th January 2020) - Morishita, Asahiro; Ogawa, Chikara; Moriya, Akio; Tani, Joji; Yoneyama, Hirohito; Fujita, Koji; Oryu, Makoto; Senoo, Tomonori; Takaguchi, Koichi; Masaki, Tsutomu
Abstract : Aim: The incidence of hepatitis C virus (HCV) infection is much higher in hemodialysis patients than that in healthy individuals. The prognosis of hemodialysis patients with HCV infection is poorer than that without HCV infection. Therefore, antiviral intervention is pivotal for HCV infection in hemodialysis patients. Recent evaluations of the pangenotypic regimen of glecaprevir/pibrentasvir show that it is highly effective and safe for HCV‐infected hemodialysis patients. However, a few reports showed that the effect of HCV elimination by glecaprevir/pibrentasvir improved liver dysfunction or anemia. The aim of the present study was to determine clinical outcomes after HCV elimination using the glecaprevir/pibrentasvir regimen in HCV‐infected hemodialysis patients. Methods: This study was a retrospective, six‐center study conducted in Japan, in which 24 hemodialysis patients with HCV genotype 1–2 treated with glecaprevir/pibrentasvir were recruited. Blood examinations were performed at end of treatment (EOT), and at 3, 6, and 12 months post‐treatment during the 12‐month follow‐up period. Results: The overall sustained virologic response rate was 100% (24/24). During the DAA treatment period, adverse events were observed in 20.8% of patients (5/24), and pruritus was the most frequently observed in 12.5% (3/24). Interestingly, we observed an improved control of anemia after EOT with a significant increase in hemoglobin levels. In addition, total bilirubin was diminished, and platelet counts and albumin, total cholesterol, and alpha‐fetoprotein levels remained unchanged after EOT in hemodialysis patients. Furthermore, erythropoietin concentration was not increased after EOT. Conclusions: HCV elimination using glecaprevir/pibrentasvir treatment might be a major breakthrough for the control of anemia in hemodialysis patients.